Analysis of Perforated Steel Unequal Angle Members by using Abaqus - Prof. H. Sudarsana Rao, E. Sarath, Dr. Vaishali. G. Ghorpade (International Journal of Advanced Science and Technology, 2019)
Hot -rolled steel angle sections has many structural applications in industrial plants and lattice power transmission towers. In industries they are used as supporting structures to pipes and elevators, shelves, roof trusses, chimneys, silos, overhead tanks, bunkers and storage pallet racks etc. They are frequently used in roof and lateral braces in industrial structures. Previously for the performance assessment of angle members under compression researchers developed many analytical and experimental methods. The design of angle members are difficult to understand even they have simple structural shape and used in a variety of applications, so they should be examined thoroughly from the designer’s point of view as there is no sufficient experimental data available for angle members in comparison with other standard structural shapes. This paper is concerned with the ultimate load capacity of non-perforated and perforated equal & unequal-angle hot rolled steel columns. A finite element analysis has been undertaken to investigate the behaviour of such members. The software used for finite element analysis in this work is ABAQUS. Keywords: Staggered Pattern, Uniform Pattern, Loaded Leg, Unloaded Leg, imperfections, perforations.